TASAMUH VILLAGE: A MODEL OF REALIZING TOLERANCE VALUES AS AN ANTIDOTE TO INTOLERANCE TO REALIZE RELIGIOUS MODERATION IN INDONESIA - Mhd. Rasidin; Luqyana Azmiya Putri; Nurul Alamin; Doli Witro (Khatulistiwa, 2023)
This article describes the actualization of tasamuh values to be applied among religious people in Indonesia. Tasamuh is one of the attitudes that teach humans to be tolerant and fair, respect each other, and respect differences. However, it should be highlighted that the principle of tasamuh in Islam does not touch the field of faith but is actualized in the frame of brotherhood among human beings. In line with that, to meet the religious moderation program campaigned by the government, it is even stated in the National Medium-Term Development Plan (RPJMN) for 2020-2024. Thus, this article offers the concept of Kampung Tasamuh. The concept of Kampung Tasamuh mainstreams the principle of inter-religious openness. Everyone who lives in a village respects and respects each other regardless of differences. Everyone has the same opportunity to voice freedom of opinion and belief using dialogue in humanitarian matters. The findings of this article The concept of Kampung Tasamuh can be applied in tandem with several principles, namely intellectual humility, cultural empathy (caring for others), and open-mindedness (thinking inclusively).